التنظيم المؤسس للأوقاف في الجزائر: الواقع وآفاق التطوير: The Founding Organization of The waqf in Algeria: Reality and Prospects for Development - Ammar, Hayet si; Boukerousha, Halima; Soualhi, Asma Akli (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
This research paper aims to explain the founding organization of the waqf in Algeria since the Ottoman period, which has evolved and risen because of interest in charitable work and the seriousness of work and perseverance in improving it Responding the needs of society inside and outside the country, after it was during the occupation and neglected after independence and suffering from legislative deficiency and administrative and organizational weaknesses, the research problem arises knowing the organizational methods through which the waqf can be revived by Algeria and sector advancement, and how can we benefit from the previous experience of waqf in Algeria during the Ottoman era. following the deductive, descriptive, and historical method. The study concluded that the best solution to develop the waqf and management in parts is to consider and improve the legal and legislative system for it and to develop administrative performance, specialization, and seriousness in work, adopting the best and latest developmental investment methods to waqf and keep pace with the leading countries.